25‐OH vitamin D level has no impact on the efficacy of antiviral therapy in naïve genotype 1 HCV‐infected patients. Issue 1 (1st February 2017) - Belle, Arthur; Gizard, Emmanuel; Conroy, Guillaume; Lopez, Anthony; Bouvier‐Alias, Magali; Rouanet, Stéphanie; Peyrin‐Biroulet, Laurent; Pawlotsky, Jean‐Michel; Bronowicki, Jean‐Pierre
Abstract : Background and aim: The impact of 25‐OH vitamin D on sustained viral response (SVR) to antiviral therapy and on fibrosis progression in hepatitis C is debated. We assessed the impact of 25‐OH vitamin D concentration on the efficacy of antiviral therapy in naïve genotype 1 hepatitis C virus (HCV)‐infected patients. Methods: The study population consisted of treatment‐naïve genotype 1 patients enrolled in a randomised controlled trial. A total of 516 patients received peginterferon α‐2a 180 µg/week plus ribavirin 800 mg/day for 24 weeks. There were 349 patients with undetectable HCV RNA (<50 IU/ml) at week 24 (W24) who were randomised to continue dual therapy ( n  = 173) or to continue peginterferon alone ( n  = 176) until week 48. 25‐OH vitamin D concentration was measured at baseline in frozen serum. Results: A total of 461 patients could be analysed for virologic response at W24, and 285 (119 non‐responders at W24 + 166 responders who continued dual therapy until W48) for the impact of SVR. There were 487 patients who could be analysed for fibrosis progression. Metavir fibrosis scores (centralised analysis) were: F1 30%, F2 34%, F3 27% and F4 9%. Median 25‐OH vitamin D concentrations were similar in virologic responders (13.5 ng/ml) and in non‐responders at W24 (12.6 ng/ml), as well as in patients with SVR (12.8 ng/ml) and without SVR (12.8 ng/ml, 3.99) at W72. Median 25‐OH vitamin D concentrations were: F1: 14.30 ng/ml, F2: 13.50 ng/ml, F3: 13.30 ng/ml and F4: 12.80 ng/ml. Conclusion: In this study, 25‐OH vitamin D level has no impact on the efficacy of antiviral therapy in naïve genotype 1 HCV‐infected patients.